Analisis Hukum Terhadap Penipuan Dengan Modus Donasi Online Berdasarkan Undang-Undang Nomor 19 Tahun 2016 - Ghozali, Ahmad; Faridah, Hana (Jurnal Ilmiah Wahana Pendidikan, 2023)
The rise of fraud in the digital era has forced the government to prepare regulations in line with the development of fraudulent technology in accordance with Law Number 11 of 2008 in conjunction with Law Number 19 of 2016 Concerning Electronic Information and Transactions, article 28 paragraph 1 states, "Every person intentionally and without the right to spread false and misleading news that results in consumer losses in electronic transactions”. This study aims to discuss legal protection for victims in online donation cases and whether misappropriation of donations or crowdfunding can be categorized as fraud in Indonesian criminal law. 1 shall be punished with a maximum imprisonment of six years and/or a maximum fine of IDR 1 billion. has set a number of implementation guidelines in determining whether or not someone violates Article 28 paragraph 1 of the Electronic Information and Transaction Law.